Addendum: Reading and studying on the screen - Mark Nichols (Journal of Open, Flexible and Distance Learning, 2018)
In 2016 the article “Reading and Studying on the Screen: An Overview of Literature Towards Good Learning Design Practice” was published in the Journal of Open, Flexible and Distance Learning (Nichols, 2016b). The article overviewed comparative studies related to reading from the screen and reading from print, and proposed recommendations for on-screen learning design. This addendum to that article considers various additional studies analysed in subsequent blog posts (see http://tel-lingit.blogspot.com/2018/02/an-update-to-reading-and-studying-from.html and https://tel-lingit.blogspot.com/2018/11/a-further-update-to-reading-and.html) up to end November 2018. As this is an invited addendum, I take the opportunity to adopt a more personal and self-disclosing style to talk more about my own position and experience regarding digital education and on-screen reading. This piece alternates across the scholarly and polemic.